2017
DOI: 10.21276/aimdr.2017.3.6.sg3
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Pathological Comparative study in patients undergoing Open Vs Laparoscopic Cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy has now replaced open cholecystectomy as the first-choice of treatment for gallstones and inflammation of the gallbladder unless there are contraindications to the laparoscopic approach. The present study is done to know the incidence of cholelithiasis in India with respect to age and sex. To compare and evaluate the advantages and disadvantages of laparoscopic versus open cholecystectomy surgical procedures. Methods: This is a comparative study done at tertiary care ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…All the patients were managed conservatively. Similarly, Lohiya et al [19] reported minimal post-operative complications with LC. They observed that 2 patients had prolonged bile leak, and 1 each had post-operative hemorrhage and surgical site infection, and all patients were treated conservatively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…All the patients were managed conservatively. Similarly, Lohiya et al [19] reported minimal post-operative complications with LC. They observed that 2 patients had prolonged bile leak, and 1 each had post-operative hemorrhage and surgical site infection, and all patients were treated conservatively.…”
Section: Discussionmentioning
confidence: 86%
“…None of the patients had suspected complications of AC and thus, CT of abdomen was not performed. Similarly, Lohiya et al [19] and Haziraka et al [27] used USG of abdomen as the main investigation to diagnose GS disease and reported the presence of GS in all the patients. However, Terho et al [14] reported that, even if USG is the main choice of imaging in patients with clinical suspicion of AC, they used CT in patients who presented with severe or diffuse symptoms, and magnetic resonance imaging in patients with suspicion of bile duct stones, in addition to AC.…”
Section: Discussionmentioning
confidence: 99%